SAT0088 First year rapid radiological progression is the best predictor of further progression in early arthritis: Results of the ESPOIR cohort. (23rd January 2014) - Tobon, G.; Saraux, A.; Lukas, C.; Gandjbakhch, F.; Mariette, X.; Combe, B.; Devauchelle-Pensec, V.
Abstract : Background: One of the major goal in the treatment of early arthritis is to prevent articular destruction. Several factors predicting joint destruction have been identified but the rapidity of progression during the first year has never been evaluated. Objectives: To determine in a large cohort of early arthritis, if the rapid progression during the first year was a predictor of further rapid progression during the next two years. Methods: 813 patients with arthritis of less than 6 months were included in the prospective French "ESPOIR" cohort. Standardized radiographs of hand, wrist and foot in postero-anterior view (PAV) were performed at inclusion, one, two and three years. Inter and intraobserver variabilities were assessed. All the radiographs were examined by a blinded reader for modified Sharp score. The speed of progression was defined at one year (between M0 and M12: FIrst year Radiological Evolution (FIRE)) and after the next two years (between M12 and M36: (FUrther Radiographic Evolution (FURE)). The patients with a speed of annual progression of more than 2.5 in the erosion or joint space narrowing and 5 for the total Sharp score were considered as rapid progressor (rp). Results: 535 patients have a complete set of radiographs. Among them 7% (35/500) received biological treatment before one year. None of them had FURE-rp erosion. For the 500 remaining patients without biologics, the correlation between narrowing and erosion progression during the first year was low (r: 0.3). During the first year, 37/500 (7.4%) did not have radiographic progression and 25% (123/500) were rapid progressor. During the following years, 53/500 (10.5%) had FURE-rp for erosion, 146/500 (29%) and 92/500 (18.4%) for total Sharp score. The presence of RF or ACPA in both set of classification criteria (1987 ACR or ACR/EULAR criteria), and the item 7 of the 1987 ACR criteria were associated with FURE-rp for erosion narrowing or total score. FIRE erosion, narrowing or total score were associated with all FURE-rp (p<0.0001). Using logistic regression, FURE-rp erosion was best predicted by the serological item, the level of Il-6, FIRE-rp for total score and erosion at inclusion. FURE-rp narrowing was predicted by the serological item, the level of Il-6 and FIRE-rp total score. FURE-rp total score was predicted by the serological item, the level of Il-6, FIRE erosion and erosion at inclusion. When items were combined, the FIRE criteria performed better than other criteria to predict FURE-rp. Conclusions: The first year radiological progression is an independent predictor of further rapid progression in early arthritis. Disclosure of Interest: None Declared